Determination of the compression index of reconstituted clays using intrinsic concept and normalized void ratio - Habibbeygi, F.; Nikraz, Hamid; Verheyde, F. (The Geomate International Society, 2017)
Measurement of the compression indexes of clayey soils, particularly reconstituted clays with a high initial water content, is generally time-consuming and costly. A mitigation of these constraints could include a correlation between the compression indexes and the consistency limits of the clay soil that can be measured reliably. In this paper, the time-tested concepts of intrinsic framework and normalisation methods were used to derive a correlation between the compression indexes of reconstituted clays and the soil void ratios at consistency limits. The proposed method is based on the assumption that a unique relationship exists between consolidation pressures and consistency limits. Furthermore, the equation was simplified to estimate the compression index as a function of consistency indexes. Then, the equation was validated via comparison with a wide range of results reported in the literature regarding various types of clay. Results of this comparison suggest that there is an exclusive relationship between compression index and consistency limits for reconstituted clays.